POLA ARGUMEN PARAGRAF ARGUMENTATIF PADA ARTIKEL JURNAL TERAKREDITASI BIDANG EKONOMI (PERSPEKTIF STEPHEN TOULMIN) - Setyaningsih, Yuliana (Adabiyyāt: Jurnal Bahasa dan Sastra, 2016)
This research is aimed at finding patterns of arguments of argumentative paragraphs in the discussion parts of accredited economic journal articles. The research result shows that patterns of arguments can be differetiated into six, namely (1) Claim-Data; (2) Claim–Data 1–Data 2; (3) Data–Claim; (4) Data 1 – Data 2 – Claim; (5) Data 1– Data 2 – Data 3 – Data 4 – Data 5- Warrant – Claim; (6) Data 1 – Data 2 – Claim – Data 3 – Data 4 – Data 5. Thus it can be concluded that argument patterns of economic journal articles must be continuously increased. The effort of increasing quality of journal articles is considered urgent since Indonesian scientists who contribute ideas through writing journal articles will automatically increase scientific participation in the academic realm broadly.